Four-Element Composite Triangular Dielectric Resonator Antenna Using Li2O-1.94MgO-0.02Al2O3-P2O5 Ceramic for Wideband Applications - Kumari P.; Tripathi P.; Sahu B.; Singh S.P.; Kumar D. (My University, 2025)
A simulation and fabrication study of a coaxial probe-fed four-element composite triangular dielectric resonator antenna (TDRA) using low loss Li2O-1.94MgO-0.02Al2O3-P2O5 (LMAP) ceramic and Teflon. LMAP ceramic was carried out and the ceramic was synthesized using a solid-state sintering route. The phase, microstructure and microwave dielectric properties of LMAP were investigated using x-ray diffraction pattern, scanning electron microscopy and a network analyzer. A coaxial probe-fed four-element composite TDRA was designed and fabricated using LMAP as one section of each composite element of the proposed antenna. Each triangular element of the proposed dielectric resonator antenna (DRA) consists of two sections of different dielectric constant materials. The inner triangular section touching the coaxial probe at one of its corners is made of the LMAP ceramic (εr = 6.2) while othe uter section is made of Teflon (εr = 2.1). Four triangular DRA elements are excited bya centrally located 50-Ω coaxial probe. The parametric study of the proposed antenna was performed through simulation using Ansys High Frequency Structure Simulator software by varying the dimensions and dielectric constants of both sections of each triangular element of the TDRA to optimize the results for obtaining a wideband antenna. The simulated resonant frequency of 9.30 GHz with a percentage bandwidth of 61.65% for the proposed antenna is obtained within its operating frequency range of 7.82–14.8 GHz. Monopole-like radiation patterns with low cross-polarization levels and a peak gain of 5.63 dB are obtained for the proposed antenna through simulation. The antenna prototype having optimized dimensions has also been fabricated. The experimental resonant frequency of 9.10 GHz with a percentage bandwidth of 66.09% is obtained within its operating frequency range of 7.70–15.30 GHz. It is found that the simulation results for the proposed antenna are in close agreement with the measured data. The proposed antenna can potentially be used in broadcast base stations, radar and satellite communications. © 2018, The Minerals, Metals & Materials Society.